Feasibility Analysis of Tofu Agroindustry Business (Case Study of Sederhana Tofu Factory in Bukit Peninjauan I Village, Sukaraja District, Seluma Regency, Bengkulu Province) - Sarina Sarina; Ikhsan Hasibuan (Jurnal Penelitian Pertanian Terapan, 2023)
Sederhana Tofu Agroindustry is the biggest tofu factory in the village of Bukit Peninjauan I. It produces tofu each day in order to fulfil the need of two major traditional markets in Bengkulu city. This research aimed to analyze the financial feasibility of Sederhana tofu agroindustry in Bukit Peninjauan I Village, Sukaraja District, Seluma Regency. The research had been done on May until July 2021. The data were analyzed by using descriptive and quantitative analyzed methods. The descriptive analysis was used to investigate the common states of the research object, including characteristics and non-financial aspects. Meanwhile, the quantitative anayisis meant to evaluate the company financial conditions such as NPV, IRR, Net B/C, and Payback Period. Based on our analyzing, we wrap up that this agroindustry is feasible to be performed and to be developed. Some aspects that support this that the tofu agroindusty achieved good criteria, including had NPV for about Rp . 1.361.902.000,- IRR 27,87%, Net B/C 1,38 and PP 4,93 years. Keywords : agroindusty, feasibility, financial, tofu